Pengungkapan Islamic Social Reporting pada Perusahaan di Jakarta Islamic Index - Khaerun Nissa Rizfani; Deni Lubis (Department of Islamic Economics, IPB University, 2018)
Islamic Social Reporting (ISR) is a benchmark for reporting Islamic-based social performance to companies. However, the development of ISR is currently not growing rapidly in Indonesia because there are no regulations that regulate sharia social responsibility reporting standards. Increased disclosure of Islamic social performance is expected to influence the decisions of muslim investors in choosing sharia shares in companies listed in the Jakarta Islamic Index. This study aims to analyze corporate social responsibility (CSR) disclosures in sharia and the factors that influence them. The data used are annual reports of companies registered in JII from 2012 to 2015, 14 of which were selected from 30 companies. The method used in this study is panel data regression with the fixed effect model (FEM) approach. The results of the analysis show that of the five variables that allegedly influence the level of ISR disclosure, three variables, namely company size have a positive effect, firm age and leverage have a significant negative effect on ISR disclosure. The other two variables, namely the number of board of commissioners and profitability have no effect on ISR disclosure.